An observational study on the effect of stent microbial culture status on double J stent associated lower urinary tract symptoms - Rassol, Mustaq; Praveen, A. P. S. Guru; Shaik, Jamal; Laxmi Ramesh, M.; Vedamurthy Reddy, P. (International Journal of Research in Medical Sciences, 2024)
Background: The double-J ureteral stent had been widely applied during the endourologic surgery to relieve or prevent ureteral obstruction. Stent-related morbidities, such as lower urinary tract symptoms (LUTS), stent-related body pain and hematuria, are bothersome and might have a negative impact on quality of life (QoL) and sexual performance for both genders. The prevalence of LUTS after double DJ stenting is 50%-70%. The prevalence hence is significant and geographic variance might exist. This makes this issue an important health problem and indirectly serves as a scale for quality of healthcare delivery to the public. This study aimed to study the effect of stent microbial culture status on double j stent associated lower urinary tract symptoms performed at Narayana Hospitals, Nellore. Methods: An observational study was conducted in the Department of Urology, Narayana Medical College & Hospitals, Nellore for 18 months from June 2021 to November 2022. A convenient sample of 45 were selected among the patients who underwent DJ stenting and presenting with LUTS to the outpatient department. Results: The sensitivity of urine culture was 29.27%. The specificity and PPV are 100%. The NPV was 12.12% with diagnostic accuracy was 35.56%. The age and symptom score-IPSS were correlated and the r value was -0.03, QOL and Age were correlated with the r value was 0.004. Conclusions: Urine culture was positive among 26.66% and stent culture in 84% of the stents. Urine culture is highly specific in identifying the stent culture status.